Analisis Konsep Fisika Pada Proses Pengeringan Kopi Menggunakan Solar Dryer - Sa’diyah, Halimatus; Zahwa, Dhea Amanda; Sudarti, Sudarti; Mahmudi, Kendid (Peneliti.net, 2025)
Drying coffee beans with a solar dryer is a sustainable solution to improve quality and production efficiency. However, its implementation in the field faces challenges such as high material costs, design complexity, and the gap between physical principles and farmers' socioeconomic conditions. This article analyzes the physical concepts underlying coffee drying using solar dryers, including heat transfer dynamics, numerical modeling-based design optimization (CFD and FEM), and technology integration such as IoT and hybrid systems. A literature review of 20 related studies showed that while solar dryers are theoretically effective, for example through thermal efficiency improvements of up to 40% with vacuum collectors, the use of expensive materials, reliance on fossil energy in hybrid systems, and lack of technical education hinder the adoption of this technology at the farm level. The conclusion emphasizes the importance of local material-based designs such as bamboo, participatory education, and holistic policy interventions to bridge the gap between scientific innovation and field realities.